(untitled) (Al-Farooq Journal of Sciences, 2026)
Background: Oral candidiasis is an opportunistic fungal infection caused by Candida spp. Although these yeasts are a normal inhabitant of the mouth in a large percentage of people, they can become pathogenic under suitable conditions. With increasing resistance to conventional antifungals, the need to discover effective natural alternatives has become apparent. Objective: This study aimed to evaluate the inhibitory efficacy of an ethanolic extract of S. officinalis against three Candida isolates from patients with oral candidiasis. Materials and Methods: involved preparing an ethanolic extract of S. officinalis and testing the susceptibility of the isolates using the disc diffusion method, comparing the results with the efficacy of some standard antifungal agents. Results: The results showed that S. officinalis extract inhibited the growth of C. albicanis, with an average aura diameter of 19.5 ± 1.18 at 100% concentration. Compared to standard antifungal agents, the extract demonstrated superior efficacy, surpassing amphotericin B, which showed the highest effect on all three isolates. The average aura diameter for C. tropicalis was 25.17 ± 1.86 at 100%, while C. parapsilosis was the least affected by the extract. Conclusions: The study concludes that S. officinalis extract possesses antifungal properties, making it a promising alternative for developing topical treatments for oral fungal infections.